Enhanced simulation of East Asian summer precipitation with a revised simplified Arakawa–Schubert convection scheme - Shu Gui; Ruowen Yang; Lei Cai; Yali Yang; Ying Ming; Yu Lian; Meng Li; Kexu Zhu; Hao Zeng (Atmospheric Research, 2026)

SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

Particle-associated distribution, sedimentary accumulation, and SSD-based ecological risk assessment of organochlorine pesticides in the East China Sea - Jie Fu; Longkun Sun; Yan Zhang; Wenqing Wang; Zhongyu Cui; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Marine Environmental Research, 2026)

FFDNet: An end-to-end lightweight real-time fire detection model for forest fire environments - Qian Yu; Gui Zhang; Ying Wang; Xin Wu; Haizhou Xu; Wenbing Kuang; Subo He; Jiangshu Xiao; Wuyang Hu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Yield advantage in wide strip intercropping: Border-row effects and adding a third crop in double relay intercropping - Hao Yang; Huai-Ying Ma; Yi-Wen Zhao; Jiu-Dong Zhang; Gui-Zong Zhang; Jia-Kang Lu; Ya-Xian Huang; Xing-Guo Bao; Rui-Peng Yu; Wopke van der Werf; Long Li (Field Crops Research, 2026)

Legacy-to-Alternative Shift of Brominated Flame Retardants in the East China Sea Revealed by Multimedia Observations and Coupled Modeling - Jie Fu; Xing Liu; Gu Tao; Haibo Zhang; Ye Kong; Zhen He; Chun-Ying Liu; Dong-Liang Lu; Gui-Peng Yang (Water Research, 2026)

Probiotic Bacillus strains enhance cellulose digestibility and silkworms growth via gut microbiota modulation - Yueqin Jin; Ying Zhao; Chen Chen; Xueping Jiang; Sitong Chen; Ran Zhang; Hao Li; Zhongzheng Gui (Journal of Insect Physiology, 2026)

Research progress on multiscale electrospun fibers for piezoelectric nanogenerators: Structural innovation and intelligent applications - Ying Xu; Zishuo Zhang; Bowen Yao; Yueling Shen; Dong Gui; Yaoyao Yang; Yang Liu; Deng-Guang Yu; Yanan Liu (Chemical Engineering Journal, 2026)

Atrazine-modified root exudates reshape the rhizobium community and regulate soybean growth - Duo Jiang; Zhao Jiang; Wei Li; Ke Du; Yi Wu; Zhengze Du; Yining Gui; Bo Cao; Yuexuan Ma; Ying Zhang (Applied Soil Ecology, 2026)

Diffusion-attenuation characteristics of grout in water-bearing soft strata: a pressure-attenuation correction model accounting for hole depth effect - Ling Zeng; Yong-Chao Wang; Jing-Cheng Chen; Jie Liu; Li Yi; Jing Tang; Gui-Jin Zhang; Ming Fan; Cai-Ying Chen (Bulletin of Engineering Geology and the Environment, 2026)

Lauric Acid and Glycerol Monolaurate Inhibit the Activity of Cyprinid Herpesvirus 2 and Enhance Host Immune Reaction - Jiahua Zhang; Ying Qin; Mingyang Ma; Tonghui Xu; Ye Zhang; Lang Gui; Liqun Lu; Dan Xu (Journal of Fish Diseases, 2026)
Cyprinid herpesvirus 2 (CyHV‐2) is a major pathogen causing high mortality in farmed goldfish and crucian carp, for which effective prophylactic or therapeutic treatments are currently limited. Lauric acid (LA) and glycerol monolaurate (GML), representative of a medium‐chain fatty acid (MCFA) and its corresponding monoglyceride, respectively, have been reported to possess antiviral and immunomodulatory properties. This study systematically evaluated the anti‐CyHV‐2 effects of LA and GML through in vitro assays, transcriptomic profiling, and in vivo experiments. In vitro, both LA and GML significantly reduced viral copy numbers in gibel carp caudal fin (GiCF) cells, attenuated virus‐induced cytopathic effects (CPE), and suppressed intracellular viral replication. Transcriptomic analysis revealed that LA and GML induced widespread alterations in host signalling pathways, with significant enrichment of pathways related to steroid biosynthesis, ECM–receptor interaction, protein digestion and absorption, and cell survival–associated signalling. Quantitative PCR analysis further demonstrated that the expression levels of insr , akt2 , pdk1 , lamtor3 , and hsp90b were significantly upregulated, whereas inpp4b expression was downregulated. These results further validate that host cell metabolic processes, stress responses, and signal transduction pathways are substantially modulated following LA and GML treatment. The in vivo protective efficacy of GML was further assessed. In goldfish infected with CyHV‐2, GML administration significantly increased survival rate and mitigated histopathological damage in the gills, liver, spleen, and kidney. At 3 days post‐infection (dpi), expression levels of pro‐inflammatory cytokines il‐1β , il‐6 , and tnf‐α were significantly lower in the GML‐treated group compared to the virus‐infected control group, whereas the anti‐inflammatory cytokine il‐10 was significantly upregulated. By 7 dpi, differences in inflammatory cytokine expression between groups had diminished, suggesting that GML not only exerts direct antiviral activity but may also modulate host immune responses during the early stage of infection. Collectively, these findings provide a theoretical basis for the practical application of LA and GML and propose a novel strategy for developing safe, effective, and environmentally friendly anti‐CyHV‐2 agents.

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Study on oxidative stress and nitric oxide response mechanisms in Gymnodinium sp. under polystyrene microplastic stress - Zhen Ren; Zheng–Xin Hu; Xue Deng; Pei–Feng Li; Chun–Ying Liu; Shan–Shan Duan; Xiang–Feng Kong; Gui–Peng Yang (Journal of Applied Phycology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Exploring the therapeutic mechanism of kaempferol in acute lung injury: Network pharmacology and experimental validation - Zhu-ying Zhou; Chen-xi Zhang; Xiu-ling Wei; Chuan-fu Wu; Da-gui Chen; Fu-sheng Shang; Chun-ming Jiang (Tissue and Cell, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Nitric oxide indicates the response of Chlorella sp. to ocean warming and its potential mechanisms - Kuo Li; Zheng-Xin Hu; Ying-Shun Wang; Hui-Min Jian; Pei-Feng Li; Chun-Ying Liu; Jing-Wen Hu; Gui-Peng Yang (Marine Biology, 2026)

Expression of Transforming Growth Factor Beta 1 in Lung Adenocarcinoma and Its Relationship with Circulating Tumour Cells - Ning Chen; Duo-Jun Qiu; Jian-Zhu Yang; Gui-Yun Zhu; Li-Fei Kang; Xiao-Ying An; Zhi-Ming Xu; Xiao-Xia Li (Biochemical Genetics, 2026)

A new chlorine-containing flavanol and four new phenylpropanoids from Toddalia asiatica - Bing-Ying Zheng; Zhan-Tao Zhao; Feng Wu; Nan An; Shu-Qi Wu; Lu Gan; Sheng Yin; Run-Zhu Fan; Gui-Hua Tang (Natural Product Research, 2026)

Undescribed triterpenoid ellagitannins from Castanopsis calathiformis and their potential antiproliferative and hypoglycemic activity - Ya-feng Wang; Ying-rong Bao; Rui-jie He; Nao Pang; Zhang-bin Liu; Bing-yuan Yang; Gui-qin Li; Yong-lin Huang (Phytochemistry, 2026)

Lactiplantibacillus plantarum 5.1 attenuates ovarian fibrosis by modulating the gut microbiota and ovarian metabolism in a rat model of letrozole-induced polycystic ovary syndrome (PCOS) - Qiu-Ping Huang; Li-Ying Huang; Gui-Lian Liao; Chun-Xiang Huang; Ke-Ying Wang; Jie-Jing Xu; Hao-Ran Sun; Tie-Min Jiang; Jia-Le Song (Food Bioscience, 2026)

Variations in semi- and non-volatile organic substances during physical recycling and their migration from rPET bottles - Yi-Qi Liu; Yan Zeng; Shao-Fu Zeng; Zhi-Wei Wang; Lei Zhu; Li-Li Jin; Gui-Qin Shang; Gui-Hua Liu; Chang-Ying Hu (Food Packaging and Shelf Life, 2026)

Synthesis of BMP wrist epitope-derived peptide functionalized bioink for 3D bioprinting of tissue-engineered bone constructs - Fei Huang; Guozhen Wei; Ying Zhang; Bing Wu; Yaoqing Chen; Yaoyu Qiu; Jingfeng Li; Gui Wu (Chemical Engineering Journal, 2026)

Stomatal width and vascular bundle anatomy govern foliar uptake and phloem transport of atmospheric Pb in wheat - Liu-Xu Feng; Xiang-Yu Li; Pei-Pei Gao; Yan Li; Gui-Li Hua; Ding-Hao Li; Li-Ping Geng; Xiao-Min Wang; Hong-J. Di; Wen-Ju Liu; Pei-Ying Xue (Journal of Hazardous Materials, 2026)

Boosting char formation in lignin aerogels via PN synergy: A route to flame retardancy and multifunctional performance - Jia-Hui Wang; Tao Gui; Shuang-Lin Zou; Qing-Hua Wang; Ying-Chun Xu; Rong Tan; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Chemical Engineering Journal, 2026)

Impact of macroalgae farming on the carbonate system and biogenic sulfur dynamics in Sansha Bay, China - Ping Wang; Zheng-Xin Hu; Yu Xin; Bing-Han Li; Lu Han; Shu-Hang Dong; Chun-Ying Liu; Tao Liu; Jing-Wen Hu; Jiang-Chen Gong; Gui-Peng Yang (Marine Pollution Bulletin, 2026)

Weyl points enabling significant enhancement of thermoelectric performance in an antiferromagnetic van der Waals metal GdTe3 - Zhigang Gui; Panshuo Wang; Wenxiang Wang; Yuqing Zhang; Yanjun Li; Yikang Li; Qingyuan Liu; Xikai Wen; Qihang Liu; Jianjun Ying; Xianhui Chen (Science Bulletin, 2026)

Genetic deletion of miR-200a/200b increases growth and feed conversion efficiency in yellow catfish - Xu Wang; Yan Xie; Qiaohong Lin; Yang Xiong; Ying Liu; Si Ge; Qiuen Tan; Zhipeng He; Youbo Jiang; Qingqing Han; Shuang Jin; Peipei Huang; et al. (Science China Life Sciences, 2026)

Computer vision-based detection and dynamic tracking of multiple micro bubbles in transparent liquid similarity experiments for SGTR in lead-cooled fast reactor - Ying Guan; Yang Li; Hualei Jiang; Daqing Wang; Daochuan Ge; Huaping Mei; Gui Fang; Lifu Gao; Haixia Wang (Annals of Nuclear Energy, 2026)

Multi-source jitter information fusion method of high-resolution optical remote sensing satellite images based on H-infinity filtering - Yanling Dong; Yingqi Tian; Ying Zhu; Guangqi Xie; Xiaoqian Li; Yuhao Gui; Xiangjun Liao; Xin Zhang (International Journal of Remote Sensing, 2026)

Foam stabilization mechanisms in blended Short-Chain alcohol and polyether surfactant systems for flotation - Mengdi Xu; Fangyu Guo; Xicheng Bao; Ying Zhou; Xiahui Gui; Yaowen Xing (Minerals Engineering, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Integrated optimization of effluent quality, energy use, and chemical dosing in wastewater treatment using a cyclic residual-steered Bayesian framework - Ke Chen; Min Yang; Ning Gui; Yu Tao; Ying Chen; Aijie Wang; Jinxiang Liu (Journal of Environmental Management, 2026)

U-shaped association between outdoor artificial light at night exposure and metabolic syndrome in Chinese youth: Findings from a nationally representative study - Wen-xin Ge; Zhao-huan Gui; Zhi-Yong Zou; Li-qing Yao; Wen-wen Bao; Le-bing Wang; Li-xin Hu; Zheng-ge Jin; Wan-xin Wu; Jun Ma; Ying-Hua Ma; Ya-jun Chen (Environmental Pollution, 2026)

Defect passivation with Pb for high-performance Sb2S3 solar cells via vapor transport deposition - Gan Huang; Xin-Yi Cai; Hu Li; Jin-Rui Cai; Ying-Sen Xia; Zhi-Ping Huang; Li-Mei Lin; Fu-Bao Gong; Shui-Yuan Chen; Gui-Lin Chen (Chemical Engineering Journal, 2026)

Spatio-temporal distribution and production-consumption dynamics of nitric oxide in coastal waters off Qingdao, China - Yun-Fei Li; Ye Tian; Hui-Min Jian; Chun-Ying Liu; Tian-Tian Ge; Pei-Feng Li; Gui-Peng Yang (Marine Environmental Research, 2026)

Vegetation and tides regulate the emissions of volatile sulfur compounds from intertidal wetland sediments - Qin‐Dao Li; Pei‐Feng Li; Chun‐Ying Liu; Jiang‐Chen Gong; Jing‐Wen Hu; Qian‐Qian Yang; Gui‐Peng Yang (Limnology and Oceanography, 2026)
Volatile sulfur compounds (VSCs)—carbonyl sulfide (COS), dimethyl sulfide (DMS), and carbon disulfide (CS 2 )—play critical roles in atmospheric chemistry. Nevertheless, quantitative understanding of VSC exchange dynamics in coastal wetland ecosystems remains limited. Here, we quantified the sediment‐air fluxes of these VSCs across vegetated ( Spartina alterniflora and Suaeda glauca ) and unvegetated mudflat habitats via year‐round field observations in a temperate intertidal wetland. We found that S. alterniflora sediments exhibited net emissions of COS (4.61 ± 9.19 nmol m −2 s −1 ), DMS (10.25 ± 12.35 nmol m −2 s −1 ), and CS 2 (5.77 ± 7.29 nmol m −2 s −1 ), while S . glauca and mudflats exhibited variable sink–source dynamics. VSC fluxes from S. alterniflora habitats significantly exceeded those from other zones due to high root sulfate and total sulfur contents, as well as microbial organisms and temperature‐dependent microbial activity related to sulfur metabolism. The DMS flux in S. alterniflora zones decreased by 33–224% after ebb tide compared to before flooding, with principal component analysis identifying phase‐specific controls: pre‐flood fluxes were associated with porewater chemistry (pH, redox potential) and atmosphere (water content, pressure) coupling, while post‐ebb fluxes were governed by ionic gradients (conductivity) and residual moisture (water content). Tidal simulation experiments revealed the joint influences of illumination, water content, and anaerobic processes on VSC production, where anaerobic conditions suppressed DMS and CS 2 formation but enhanced COS emission in the dark. These findings establish that coastal VSC fluxes are regulated by the interplay between macrophyte‐mediated sediment biogeochemistry and tidal pumping. This provides mechanistic insights into wetland sulfur cycle modeling.

Comparison of direct oxidative transfer process (DOTP) with Fenton and ozonation processes for water treatment - Zhao-Hua Wang; Gui-Xiang Huang; Ying-Jie Zhang; Hou-Wei Zeng; Tian-Wei Hua; Han-Qing Yu (Water Research, 2025)

Chemical constituents of Rhododendron virgatum Hook and their chemotaxonomic significance - Gui-fang Li; Xin Wang; Hong-ying Chen; Shuai Huang; Lin Chen; Xian-li Zhou (Biochemical Systematics and Ecology, 2025)

Circular RNA hsa_circ_0124644 regulates apoptosis of endothelial cells in coronary artery disease - Ying Cui; Boxin Zhao; Shimeng Wang; Lin Gui; Yingyu Xiang; Zhiyong Zhang; Xueyuan Sun; Jingyao Fan; Jun Liu; Lijuan Huang (In Vitro Cellular & Developmental Biology - Animal, 2025)

Transcriptomic profiling reveals mechanism, therapeutic potential, and prognostic value of cancer stemness characteristic in nasopharyngeal carcinoma - Jin-Wei Chen; Run-Nan Shen; Jiang-Quan Zhu; Ying-Hang Wang; Liang-Min Fu; Yu-Hang Chen; Jia-Zheng Cao; Jin-Huan Wei; Jun-Hang Luo; Jia-Ying Li; Cheng-Peng Gui (Functional & Integrative Genomics, 2025)

Estimating and compensating for shear-wave splitting in orthotropic media - Hai-feng Chen; Peng-yuan Sun; Xiang-yang Li; Zhong-ping Qian; Jian-lei Zhang; Gui-ling Zhao; Xiao-ying Qin (Applied Geophysics, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Comparative study on the structural, antioxidant and functional properties of hydrolysates from Pleurotus erynigii and Pleurotus ostreatus protein by alcalase and trypsin - Xiao-Xuan Hou; Shu-Jing Bing; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang; Hai-Zhen Mo (Food Bioscience, 2025)

Two new N -containing heterocyclic compounds from the roots of Platycodon grandiflorus - Lan Ding; Xin-Yin Cai; Ren-Nai Yang; Liang-Ping Zha; Shuang-Ying Gui; Jin-Song Liu; Ju-Tao Wang; Yang Yu (Natural Product Research, 2025)

Co-inoculation of protist and Bacillus enhances plant growth via reshaping rhizosphere bacterial community composition and function - Qihui LÜ; Chen LIU; Ying GUI; Yang YUE; Xiao WANG; Zeyuan ZHOU; Ying YUAN; Yijing WANG; Boting XU; Zhihui XU; Mohammadhossein RAVANBAKHSH; Alexandre JOUSSET; et al. (Pedosphere, 2025)

Thiourea-modified magnetic sodium alginate pellets for passivation of lead and cadmium in soil: Preparation, properties, and mechanisms - Fansong Meng; Hang Gao; Nanfang Wang; Yuwei Liao; Xuanyu Su; Jing Gui; Jianhua Qu; Hongli Fan; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Steroid hormones and their combinations affect circadian rhythm pathway in F0 Gambusia affinis using transcriptome sequencing: validation by life-long exposure of F1 offspring and molecular dynamics - Guo-Yong Huang; Gui-Zhen Fang; Shi-Quan Zou; Guang-Guo Ying (Environmental Pollution, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Morphological feature assessment of Larimichthys crocea for quality grading: a computer vision approach - Dejun Feng; Hang Liu; Lianhui Wu; Xiaoguo Ying; Xiaoyu Qu; Yang Gao; Fukun Gui; Chao Zhou (Aquaculture International, 2025)

Assessment of the efficacy of Corbicula fluminea in controlling Ichthyophthirius multifiliis infections - Tian Qin; Yang-Yang Pan; Ke Huang; Wei-Shan Zhao; Ying-Zi Pan; Hong Zou; Wen-Xiang Li; Shan-Gong Wu; Gui-Tang Wang; Ming Li (Aquaculture, 2025)

Efficient phosphate removal from wastewater using Mg/Fe-functionalized tea stalk biochar through green synthesis and bio-assembly method - Huiyao Li; Shuai Shi; lrina lvshina; Ziyan Wang; Jing Gui; Ruolai Wang; Chunyu Pan; Yiwen Ning; Jianhua Qu; Siyue Han; Ying Zhang (Process Safety and Environmental Protection, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

Differences in Baijiu brewed by the same process under different ecological conditions: An example of Sichuan xiaoqu Qingxiang type Baijiu - Fuqiang Xiong; Qiao Huang; Yichen Mao; Yuan Rao; Ying Han; Xuemei Gui; Lei Tian; Xiaobing Liu; Jiayan Shao; Tongwei Guan (Food Bioscience, 2025)

Regulation of coupled carbon‑sulfur interactions by Spartina alterniflora via physicochemical properties and microorganism-mediated pathways in coastal wetlands - Yu-Xiang Zhu; Pei-Feng Li; Chun-Ying Liu; Jiang-Chen Gong; En-Ren Zhang; Jing-Wen Hu; Qian-Qian Yang; Gui-Peng Yang (Chemical Geology, 2025)

Metagenomic profiling of pigeon faecal microbiota: insights into microbial diversity, pathogens, and antimicrobial resistance genes - Gui Ying Fong; Kok Gan Chan; Wei Lim Goh; Moh Lan Yap (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Synergistic collaboration of stirred mill and saline water to improve flotation decarburization efficiency of coal gasification fly ash - Zhenchao Ma; Zhe Li; Yingying Wang; Mengdi Xu; Ying Zhou; Xuesong Yang; Lei Wang; Yaowen Xing; Bobo Zhou; Xiahui Gui (Minerals Engineering, 2025)

Passion fruit peel pectin improves glucose and lipid metabolism in high-fat diet-induced obesity through gut microbiota and insulin sensitivity regulation - Ying Ju; Liling Huang; Hailing Luo; Yongcai Huang; Xianya Huang; Ge Chen; Jie Gui; Shengli Lin; Xuzhou Liu; Liu Yang (Food Bioscience, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Warming exacerbates the effects of pesticides on the soil collembolan gut microbiome and antibiotic resistome - Ya-Ning Wang; Tian-Gui Cai; Ying Li; Wen-Cai Dai; Da Lin; Jin-Ting Zheng; Yi-Fei Wang; Dong Zhu (Journal of Hazardous Materials, 2025)

Potential mechanism of dietary palm kernel meal effect on muscle tenderness in Tibetan sheep revealed by proteomics and phosphorylated proteomics - Ying Ma; Lijuan Han; Shengzhen Hou; Linsheng Gui; Zhenzhen Yuan; Shengnan Sun; Chao Yang; Zhiyou Wang; Baochun Yang (Food Chemistry, 2025)

Peppermint essential oil: Disruption of cellular structure and function in Listeria monocytogenes - Chun-Ling Yang; Man Hao; Jie Yang; Gui-Jin Sun; Ying-Qiu Li; Chen-Ying Wang; Yan Liang (Food Bioscience, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Nanomedicine constructed with plant-derived aromatic aldehydes treats low back pain by reversing the progression of lumbar facet joint osteoarthritis - Ming Yang; Hui Lv; Zhenzhen Tang; Jiangling Zhou; Qiandong Yang; Juan Cai; Yingtao Gui; Bo Yu; Rong Huang; Jing Yang; Ying Bao; Dinglin Zhang; et al. (Chemical Engineering Journal, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Establishment and Application of a Rapid Detection Method of Cyprinid Herpesvirus 2 ( CyHV ‐2) in Aquacultural Waters by Using a Novel One‐Pot RAA ‐ CRISPR /Cas12a Combined With Fe‐Iron Flocculation Technology - Zewei Hou; Zhaoyang Ding; Ye Zhang; Binghui Pang; Lang Gui; Ying Liu; Liqun Lu; Patarida Roengjitd; Hao Wang (Journal of Fish Diseases, 2025)
Cyprinid herpesvirus 2 (CyHV‐2) poses a substantial global threat to goldfish ( Carassius auratus ) and crucian carp ( Carassius carassius ). Despite the development of several sensitive molecular diagnostic techniques, there is an ongoing demand for alternative visualisation platforms to streamline the workflow, enhance safety profiles, and improve accessibility for end‐users. In this study, we have integrated recombinase‐aided amplification (RAA) technology with the CRISPR/Cas12a system to establish a rapid diagnostic system for CyHV‐2, termed one‐pot RAA‐CRISPR/Cas12a. This method enables the results of detection within 60 min. The RAA‐CRISPR/Cas12a platform is capable of detecting as few as 10 copies of CyHV‐2 per reaction cycle without exhibiting cross‐reactivity with other pathogens. The positive detection rate in clinical samples exceeds that of conventional PCR approaches, underscoring its high precision. Furthermore, the method could be used in conjunction with iron flocculation for the concentration and detection of viruses within aquaculture settings. This approach minimises the dissection of aquatic organisms, thereby maximising animal welfare and bolstering detection efficiency. Collectively, our findings validate the RAA‐CRISPR/Cas12a method as a robust, specific, confirmatory, user‐friendly and promising approach for on‐site diagnosis of CyHV‐2.

Impact of salinity gradients on nitric oxide emissions and functional microbes in estuarine wetland sediments - Jiang-Chen Gong; Bing-Han Li; Chun-Ying Liu; Pei-Feng Li; Jing-Wen Hu; Gui-Peng Yang (Water Research, 2025)

Numerical study of deformation inhomogeneity and its effect on mechanical properties of the heavy-wall offshore pipeline fabricated by different processes - Ling-zhi Xu; Gui-ying Qiao; Ying-long Ma; Yu Gu; Kai Xu; Xiao-wei Chen; Fu-ren Xiao (Ocean Engineering, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Voagafries A–E, undescribed indole alkaloids with anti-glioma activity from Voacanga africana - Cai-Feng Ding; Ma-Long Qin; Kun-Ying Zhao; Wen Gao; Shan-Ze Yin; Xian-Guang Hu; Gui-Guang Cheng; Rong-Ping Zhang; Wei-Yan Hu (Phytochemistry, 2025)

Optimized carbonylation treatment of Litopenaeus vannamei matrix decreased its immunoreactivity and improved edible quality, simultaneously - Meng Liu; Ming-Xuan Wu; Fei-Fei Gong; Zhao-Min Sun; Ying Li; Fei Huan; Gui-Xia Chen; Qing-Mei Liu; Hong Liu; Guang-Ming Liu (Food Chemistry, 2025)

Nitric oxide release as a defense mechanism in marine microalgae against microplastic-induced stress - Ying-Shun Wang; Zheng-Xin Hu; Hui-Min Jian; Pei-Feng Li; Chun-Ying Liu; Gui-Peng Yang (Environmental Pollution, 2025)

Sulfur metabolism and response to light in Ulva prolifera green tides - Lu Han; Yu Xin; Jinyan Wang; Pei-Feng Li; Tao Liu; Shan-Shan Duan; Chun-Ying Liu; Gui-Peng Yang (Environmental Pollution, 2025)

Ultra-low energy wastewater remediation: Excellent properties of smart adsorption membranes - Yun-Hao Xia; Ying-Ying Gui; Jia-Hua Zhou; Gui-E Chen; Zhe-Ru Shi; Zhen-Liang Xu (Chemical Engineering Journal, 2025)

Diagenetic cycling and diffusive/benthic fluxes of iron and manganese in sediments of a large semi-enclosed sea remote to major rivers - Wen-Xuan Sun; Mao-Xu Zhu; Gui-Peng Yang; Tie Li; Qing-Qing Li; Zhen Xu; Ying-Jian Han (Chemical Geology, 2025)

Digital one-pot SHERLOCK assisted superfast and reverse transcription free method for circulating microRNA absolute quantification - Zheyu Zou; Juxin Yin; Liping Xia; Weihong Yin; Ke Liu; Yating Pan; Kai Hu; Yehong Gui; Jianjian Zhuang; Duo Xiao; Ying Mu (Chemical Engineering Journal, 2025)

Inter-annual and spatial variations of air-sea CO2 fluxes and acidification mechanism in the coastal waters of Qingdao, China during 2011–2019 - Zheng-Xin Hu; Tie Li; Tian-Tian Ge; Jing-Wen Hu; Ping-Wang; Chun-Ying Liu; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Nitrogen oxides emissions from coastal wetland sediments: Experimental assessment of the influence of vegetation and nitrogen input - Jiang-Chen Gong; Bing-Han Li; Chun-Ying Liu; Qin-Dao Li; Jing-Wen Hu; Pei-Feng Li; Dan He; Gui-Peng Yang (Science of The Total Environment, 2024)

Super alkali-resistant PVDF membranes modified by coating and grafting with self-healing ability operate efficiently in the treatment of dye/water under pHs - Yun-Hao Xia; Ying-Ying Gui; Jia-Hua Zhou; Gui-E Chen; Zhen-Liang Xu (Journal of Water Process Engineering, 2024)

Hydrazino-containing Zr-MOF for enhanced Lewis acid-base catalysis of CO2 fixation into cyclocarbonate - Fangfang Li; Shasha Yun; Liping Gui; Ying-Hua Zhou (Journal of Environmental Chemical Engineering, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Complete genome sequence provides information on quorum sensing related spoilage and virulence of Aeromonas salmonicida GMT3 isolated from spoiled sturgeon - Lei Liu; Jun Li; Mingxia Tu; Liang Gao; Ying Zhang; Yu Rao; Lei Rao; Meng Gui (Food Research International, 2024)

The potential of glycinin basic peptide derived from soybean as a promising candidate for the natural food additive and preservative: A review - Hou-Qi Ning; Hai-Run Fan; Chun-Ling Yang; Gui-Jin Sun; Ying-Qiu Li; Hai-Zhen Mo (Food Chemistry, 2024)

Transcriptome analysis of Scylla paramamosain hepatopancreas response to mud crab dicistrovirus-1 infection - Min-Ze Liao; Chang-Hong Cheng; Gui-Ying Li; Hong-Ling Ma; Guang-Xin Liu; Si-Gang Fan; Yi-Qin Deng; Jian-Jun Jiang; Juan Feng; Zhi-Xun Guo (Fish & Shellfish Immunology, 2024)

Regulation of seawater dissolved carbon pools by environmental changes in Ulva prolifera originating sites: A new perspective on the contribution of U. prolifera to the seawater carbon sink function - Bing-Han Li; Jiang-Chen Gong; Cheng-Xuan Li; Tao Liu; Jing-Wen Hu; Pei-Feng Li; Chun-Ying Liu; Gui-Peng Yang (Environmental Pollution, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Mildly preheating induced conformational changes of soy protein isolates contributed to the binding interaction with blueberry anthocyanins for stabilization - Siyi Tang; Xu Si; Zhihuan Zang; Hailong Gui; Xu Xie; Liang Wang; Ying He; Baoru Yang; Bin Li (Food Hydrocolloids, 2024)

New terpenoids from Callicarpa nudiflora and their chemotaxonomic significance - Xue-Ying Lin; Gui-Fei Chen; Zi-Xiao Jiang; Yi-Tao Xing; Yang-Yang Liu (Biochemical Systematics and Ecology, 2024)

Synergistic structure engineering and electrochemical activation modulating vanadium oxide cathode toward superior zinc-ion storage - Kan Fang; Heng Zhang; Peng Chen; Hua-Yu Zhang; Zhan Wei; Ling Ding; Xiao-Ai Ye; Jiawang Liu; Yi-Lin Liu; Gui-Gen Wang; Hui Ying Yang (Chemical Engineering Journal, 2024)

Improving effect of N-acetylcysteine on growth and intestinal health in juvenile Cyprinus carpio involve the Nrf2/MAPK/NF-κB pathways - Rui Zhu; Deng-Lai Li; Bao-Yuan Zhang; Liang Li; Guo-Jun Shang; Hao-Tong Wang; Zhi-Yong Yang; Xiao-fang Wei; Si-Tong Meng; Si-Ying Liu; Yin-Tao Wang; Li-Fang Wu; et al. (Aquaculture, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Two new Stictidaceae species from grasslands in Yunnan province, China - Ying Gao; Vinodhini Thiyagaraja; Prapassorn Damrongkool Eungwanichayapant; Antonio Roberto Gomes de Farias; Jian-chu Xu; Heng Gui; Dhanushka N. Wanasinghe (New Zealand Journal of Botany, 2024)

Foliar uptake screening: A promising strategy for identifying wheat varieties with low lead accumulation - Liu-Xu Feng; Yu-Ning Li; Li-Ping Geng; Pei-Pei Gao; Xiang-Yu Li; Ding-Hao Li; Gui-Li Hua; Quan-Li Zhao; Wen-Ju Liu; Pei-Ying Xue (Science of The Total Environment, 2024)

Physicochemical characteristics of grease-trap wastewater with different potential mechanisms of FOG solid formation, separation, and accumulation inside grease traps - Ling Ying Tang; Ngie Hing Wong; Thion Am Chieng; Alex Kwong Jun Kiu; Chung Siung Choo; Yali Li; Chin Ping Tan; Abu Zahrim Yaser; Deni Shidqi Khaerudini; Gui Hua Chen; Jaka Sunarso (Water Research, 2024)

The delaying effect of Clausena lansium extract on pear ring rot is related to its antifungal activity and induced disease resistance - Wen-Wu Song; Xiao-Xiang Fu; Duan-Tao Cao; Xiao-Gui Liang; Su-Ling Xiao; Min-Xuan Yuan; Ying-Jin Huang; Qing-Hong Zhou; Hong-Yi Wei; Jun-Wen Wang; Wen-Wen Peng (Postharvest Biology and Technology, 2024)

Seven glycosides from the roots of Scrophularia ningpoensis - Ying-Ying Su; Peng Liu; Chang Xu; Gui-Yang Wang; Wei Zhang; Bin Liu (Phytochemistry Letters, 2024)

Emission of CO2 and its related carbonate system dynamics in a hotspot area during winter and summer: The Changjiang River estuary - Bing-Han Li; Hai-Long Zhao; Jiang-Chen Gong; Xi Wu; Chun-Ying Liu; Jing-Wen Hu; Gui-Peng Yang (Marine Environmental Research, 2024)

Combined effects of binary mixtures of 17β-estradiol and testosterone in western mosquitofish (Gambusia affinis) after full life-cycle exposure - Chen-Si Wang; Gui-Zhen Fang; Xiao-Pei Li; Guo-Yong Huang; Lingtian Xie; Guang-Guo Ying (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Chemical constituents from Strobilanthes cusia and their chemotaxonomic significance - Si-Qi Huang; Chao-Tian He; Qiu-Ying He; Gui-Shuai Lang; Hong-Jie Chen; Li-Ping Teng; Zhong-Bo Zhou (Biochemical Systematics and Ecology, 2024)

Observation of non-Hermitian skin effect in thermal diffusion - Yun-Kai Liu; Pei-Chao Cao; Minghong Qi; Qiang-Kai-Lai Huang; Feng Gao; Yu-Gui Peng; Ying Li; Xue-Feng Zhu (Science Bulletin, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

A siloxane-based self-healing gel electrolyte with deep eutectic solvents for safe quasi-solid-state lithium metal batteries - Yuxin Chen; Canhui Ling; Kecheng Long; Xinsheng Liu; Pengfei Xiao; Ying-Zhi Yu; Weifeng Wei; Xiaobo Ji; Wenyan Tang; Gui-Chao Kuang; Libao Chen (Chemical Engineering Journal, 2024)

Synergistic improvement of humus formation in compost residue by fenton-like and effective microorganism composite agents - Jun Zhuo Cai; Ying Lan Yu; Zhan Biao Yang; Xiao Xun Xu; Guo Chun Lv; Chang Lian Xu; Gui Yin Wang; Xin Qi; Ting Li; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Bioresource Technology, 2024)

Coating steel fiber for both CO2 capturing and strengthening of ultra-high performance concrete - Gai-Fei Peng; Gui Zhang; Hong Ding; Ying-Jie Jia (Journal of Cleaner Production, 2024)

Distribution and influencing factors of atmospheric nitrogen oxides (NOx) over the east coast of China in spring: Indication of the sea as a sink of the atmospheric NOx - Ye Tian; Hui-Min Jian; Chun-Ying Liu; Jiang-Chen Gong; Pei-Feng Li; Gui-Peng Yang (Marine Pollution Bulletin, 2024)

Mechanistic understanding of the improvement of the digestive retention of anthocyanins by modified pectin after high-pressure homogenization of strawberry pulp - Ying Xing; Qiuyan Yuan; Xiangru Gui; Lei Jian; Kunhua Wang; Qiudi Ma; Jun Wang; Huaide Xu (Innovative Food Science & Emerging Technologies, 2024)

Structural, functional and antioxidant properties of Lentinus edodes protein hydrolysates prepared by five enzymes - Shu-Jing Bing; Xing-Shuo Chen; Xin Zhong; Ying-Qiu Li; Gui-Jin Sun; Chen-Ying Wang; Yan Liang; Xiang-Zhong Zhao; Dong-Liang Hua; Lei Chen; Hai-Zhen Mo (Food Chemistry, 2024)

Interaction of 17α-ethinylestradiol and methyltestosterone in western mosquitofish (Gambusia affinis) across two generations - Guo-Yong Huang; Gui-Zhen Fang; Wen-Jun Shi; Xiao-Pei Li; Chen-Si Wang; Hong-Xing Chen; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2024)

Carbon, water and energy fluxes of terrestrial ecosystems in China - Gui-Rui Yu; Zhi Chen; Ying-Ping Wang (Agricultural and Forest Meteorology, 2024)

Unveiling the formation and magma transport dynamics of the Ulanqab maar volcanic cluster in the western North China Craton: Insights from 40Ar-39Ar geochronology, mineral chemistry, and Sr-Nd-Mg isotopes - Zong-yuan Tang; Chen-chang Chen; Si-ying Gui; Jie Li; De-you Sun; Chang-zhou Deng; Han Zheng; Guo-chun Zhao (Gondwana Research, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Investigation of lysing excess sludge slurry using hydrolase secreting thermophilic bacterial communities - Baoyan Chi; Ying Huang; Zhenfeng Xiong; Jiali Tan; Weidong Zhou; Zhuo Yang; Kemei Zhou; Xinxin Duan; Ao Chen; Rong Zha; Keting Gui (Journal of Environmental Management, 2024)

Unlocking the potential of N-acetylcysteine: Improving hepatopancreas inflammation, antioxidant capacity and health in common carp (Cyprinus carpio) via the MAPK/NF-κB/Nrf2 signalling pathway - Rui Zhu; Guo-Jun Shang; Bao-Yuan Zhang; Hao-Tong Wang; Liang Li; Xiao-fang Wei; Deng-Lai Li; Zhi-Yong Yang; Zi-Hui Qu; Ya-Nan Quan; Si-Ying Liu; Yin-Tao Wang; et al. (Fish & Shellfish Immunology, 2024)

A novel method for predicting the emergence of toxicity interaction in ternary mixtures - Jian-Ping Zeng; Jin Zhang; Jing Zhang; Xian-huai Huang; Ying Zhang; Yuan-fan Zhao; Gui-yun Hong (Environmental Research, 2024)

Two calcium-based metal organic frameworks with long afterglow as anticounterfeiting materials - Rong-Hui Shi; Zhi-Qiang Long; Fanan Wang; Ling-Zhu Gong; Xiao-Ying Lin; Gui-Lin Zhuang; Dong-Fei Lu (Chemical Engineering Journal, 2024)

Driving force of tidal pulses on denitrifiers-dominated nitrogen oxide emissions from intertidal wetland sediments - Jiang-Chen Gong; Bing-Han Li; Jing-Wen Hu; Pei-Feng Li; Qian Liu; Gui-Peng Yang; Chun-Ying Liu (Water Research, 2023)

Sludge lysis by thermophilic bacteria community enhances nutrient removal, sludge reduction, and modulates microbial community in anaerobic-anoxic-oxic process - Baoyan Chi; Ying Huang; Zhenfeng Xiong; Jiali Tan; Weidong Zhou; Zhuo Yang; Kemei Zhou; Xinxin Duan; Ao Chen; Rong Zha; Keting Gui (Journal of Water Process Engineering, 2023)

Enhanced photocatalytic performance of Mn-doped CeO2 nanoribbons for VOCs degradation: Investigating charge rearrangement and local electric field effects - Ying Wang; Yuan Lin; Jianhua Zhang; Yunyun Gui; Lijun Liu (Journal of Environmental Chemical Engineering, 2023)

Tidal effects on carbon dioxide emission dynamics in intertidal wetland sediments - Jiang-Chen Gong; Bing-Han Li; Jing-Wen Hu; Xi-Ju Ding; Chun-Ying Liu; Gui-Peng Yang (Environmental Research, 2023)

Physiological and biochemical changes in leaf abscission of Cyclocarya paliurus stem segments in vitro - Qiu-Ying Li; Shuang Wang; Gao-Yin Wu; Ya Tan; Ying-Ying Liu; Cong-Jun Yuan; Shuang-Gui Geng; Ying-Liang Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Combination of sequencing batch reactor activated sludge process with sludge lysis using thermophilic bacterial community for minimizing excess sludge - Baoyan Chi; Ying Huang; Zhenfeng Xiong; Jiali Tan; Weidong Zhou; Zhuo Yang; Kemei Zhou; Xinxin Duan; Ao Chen; Keting Gui (Journal of Environmental Management, 2023)

Two new iridoids and one new flavonoid glucoside from the tender leaves of Eucommia ulmoides and their anti-inflammatory activity - Zi-Yang Lv; Xiao-Mei Ren; Zhu-Zhen Han; Ruo-Yv Yan; Gui-Xin Chou; Ying-Bo Yang; Zi-Jia Zhang (Phytochemistry Letters, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effects of elevated temperature and acidification on sulfate assimilation and reduction of microalgae - Qin-Dao Li; Pei-Feng Li; Shan-Shan Duan; Chun-Ying Liu; Li-Jun Xie; Gui-Peng Yang (Journal of Applied Phycology, 2023)

Cell wall breaking of Haematococcus pluvialis biomass facilitated by Baijiu jiuqu fermentation with simultaneously production of beverages - Peng Zhang; Lan-Yi Lu; Shuang-Yan Liao; Gui-Ting Xu; Xin-Yi Liu; Zhang-Li Hu; Ying Xu; Li-Yan Wang (Bioresource Technology, 2023)

Clonal integration facilitates higher resistance to potentially toxic element stress in invasive alien plants than in natives - Yang Zhao; Cong-Ying Zhao; Yuan-Yuan Liu; Zhao-Gui Yan; Yong-Jian Wang (Plant and Soil, 2023)

Transcriptome analysis reveals dysregulated gene expression networks in Sertoli cells of cattle-yak hybrids - Shi-Xin Wu; Guo-Wen Wang; You-Gui Fang; Yong-Wei Chen; Yan-Ying Jin; Xue-Tong Liu; Gong-Xue Jia; Qi-En Yang (Theriogenology, 2023)

Characteristics and emissions of isoprene and other non-methane hydrocarbons in the Northwest Pacific Ocean and responses to atmospheric aerosol deposition - Ying-Cui Wu; Xu-Xu Gao; Hong-Hai Zhang; Yong-Zheng Liu; Jian Wang; Feng Xu; Gui-Ling Zhang; Zhao-Hui Chen (Science of The Total Environment, 2023)

Bisabolane sesquiterpene and cyclopentene derivatives from the marine algal-derived endophytic fungus Trichoderma asperellum EN-764 - Hong-Lei Li; Xiao-Ming Li; Zhen Ying; Yan-He Li; Bin-Gui Wang (Phytochemistry, 2023)

Exploring the continuous cleavage-oxidation mechanism of the catalytic oxidation of cellulose to formic acid: A combined experimental and theoretical study - Gui-Hua Wei; Ting Lu; Hai-Yan Liu; Jiao-Xuan Bai; Qian Wang; Guang-Yue Li; Ying-Hua Liang (Fuel, 2023)

Pentacyclic triterpenoids from spikes of Prunella vulgaris L. with thyroid tumour cell cytostatic bioactivities - Xiu-Qin Zheng; Lei-Xin Song; Zhu-Zhen Han; Ying-Bo Yang; Yi Zhang; Li-Hua Gu; Li Yang; Gui-Xin Chou; Zheng-Tao Wang (Natural Product Research, 2023)

Exposure to estrone disrupts the endocrine system of western mosquitofish (Gambusia affinis) - Dong-Qiao Lei; Guo-Yong Huang; Shu-Qing Qiu; Xiao-Pei Li; Chen-Si Wang; Gui-Zhen Fang; Lingtian Xie; Guang-Guo Ying (Aquatic Toxicology, 2023)

Development of predictive QSAR models for the substrates/inhibitors of OATP1B1 by deep neural networks - Chunshan Gui; Ying Li; Taotao Peng (Toxicology Letters, 2023)

Sex difference on fibroblast growth factors (FGFs) expression in skin and wound of streptozotocin(STZ)-induced type 1 diabetic mice - Nuo-qi Wang; Wei-hua Jia; Lin Yin; Na Li; Mei-dai Liang; Jia-min Shang; Bi-yu Hou; Li Zhang; Gui-fen Qiang; Guan-hua Du; Xiu-ying Yang (Molecular Biology Reports, 2023)

Ecological value of mariculture shellfish resources in China: Assessment and management - Chun-Yu Lin; Gui-Lin Dai; Yang Liu; Meng-Qi Zhang; Ying Liu; Wen Jiang; Xiu-Mei Fu; Han-Xue Chen (Marine Policy, 2023)

Emergent superconducting fluctuations in compressed kagome superconductor CsV3Sb5 - Xikai Wen; Fanghang Yu; Zhigang Gui; Yuqing Zhang; Xingyuan Hou; Lei Shan; Tao Wu; Ziji Xiang; Zhenyu Wang; Jianjun Ying; Xianhui Chen (Science Bulletin, 2023)

Combined Effects of Biochar-Sedum plumbizincicola on Cadmium Concentration in Cd-Contaminated Limestone Soil and Cadmium Absorption in Lactuca sativa - Ying-Ying Liu; Wen-Min Luo; Gui-Ting Mu; Xian-Liang Wu; Zhen-Ming Zhang (Water, Air, & Soil Pollution, 2023)

Perceptions of Oncology Nurses Regarding Fertility Preservation and Providing Oncofertility Services for Men of Childbearing Age with Cancer - Han-Feng Zhang; Qing-Hua Jiang; Ying-Hong Fang; Li Jin; Gui-Yu Huang; Jing Wang; Hong-Fang Bai; Mika Miyashita (Journal of Cancer Education, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Quantitative evaluation on the suitable flow region inside the shielding device of submersible aquaculture facility - Hang-Fei Liu; Ying Liu; Fukun Gui; Haofeng Sun; Yun-Peng Zhao (Ocean Engineering, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Blood trihalomethane concentrations in relation to sperm mitochondrial DNA copy number and telomere length among 958 healthy men - Chong Liu; Ying-Jun Chen; Bin Sun; Heng-Gui Chen; Vicente Mustieles; Carmen Messerlian; Yang Sun; Tian-Qing Meng; Wen-Qing Lu; Xiong-Fei Pan; Chen-Liang Xiong; Jian Hou; et al. (Environmental Research, 2023)

Transcriptome Analysis of Immune Response against Streptococcus agalactiae Infection in the Nile Tilapia GIFT Strain - Tao Zhou; Zhihua Fang; Daniel F. C. Duarte; Stefan A. Fernandes; Ying Lu; Jing Guo; Lang Gui; Liangbiao Chen (Fishes, 2022)
Streptococcus agalactiae (group B streptococcus, GBS), a broad-spectrum pathogen, causes great economic losses in fish aquaculture, especially the industry of tilapia. Until now, the knowledge of the immune response mechanism against S. agalactiae infection in tilapia has been limited. In the present study, the gill transcriptome of the tilapia from the GBS and the phosphate buffered saline (PBS) groups were sequenced. The transcriptomic analysis results presented the differentially expressed genes (DEGs) at different time points (DEGs number, 6 h: 2122, 9 h: 1851, 15 h: 1791, and 18 h: 2395) after GBS injection, and significantly enriched immune-related gene ontology (GO) terms such as the innate immune response. The significantly enriched immune pathways included the Toll-like receptor signaling pathway, the nucleotide oligomerization domain (NOD)-like receptor signaling pathway, the cytosolic-DNA sensing pathway, and the intestinal immune network for Immunoglobulin A (IgA) production. Most of the DEGs in Toll-like receptor signaling, NOD-like receptor signaling, and cytosolic-DNA sensing pathways presented upregulations at 18 h, which indicated that the innate immune pathways were activated. Two immune-related pathways (phagosome and cell adhesion molecules) were significantly enriched at all time points, suggesting that these two pathways might also play important roles in the immune response against the GBS infection. The results of HE staining showed that the gills of tilapia were damaged seriously at 9 h post-infection, which might be due to the possibility of pyroptosis resulting from the changes of DEGs in the NOD-like receptor signaling pathway. This study provided new insight into the mechanisms of gill damage in fish infected with S. agalactiae.

Chemical constituents from the Streptomyces morookaensis strain Sm4-1986 - Gui-Yun Wu; Zhi-Yan Zhu; Xiao Zhang; Miao-Miao Wang; Jian-Xiong Li; Ying-Jie Hu; Hai-Bo Tan (Natural Product Research, 2022)

Chemical constituents of Viscum coloratum (Kom.) Nakai and their cytotoxic activities - Ying-Ying Chen; Jiang-Ping Hou; Ling Huang; Afsar Khan; Fei-Fei Xing; Xiao-Han Zhang; De-Feng Han; Shi-Li Yan; Gui-Dong Cao; Qi-Yang Jiao; Dejie Liu; Xuwei Zhu; et al. (Natural Product Research, 2022)

Iridoid glycosides isolated from Nardostachys chinensis batal with NO production inhibitory activity - Gui-Min Xue; Chen-Guang Zhao; Jin-Feng Xue; Zhen-Zhu Zhao; Ying-Ying Si; Kun Du; Yan-Jun Sun; Wei-Sheng Feng (Natural Product Research, 2022)

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Production of dimethyl sulfide and acrylic acid from dissolved dimethylsulfoniopropionate during the growth of Prorocentrum minimum - Pei-Feng Li; Pei-Pei Gao; Chun-Ying Liu; Hong-Hai Zhang; Gui-Peng Yang (Journal of Applied Phycology, 2022)

Dibenzocyclooctadiene lignans from the stems of Schisandra sphaerandra - You-Min Ying; Hang-Fei Yu; Gui-Wei Rao; Jian-Wei Wang; Wei-Guang Shan; Zha-Jun Zhan (Natural Product Research, 2022)

Cloning and functional analysis of soluble acid invertase 2 gene (SbSAI-2) in sorghum - Wuyuntanmanda; Fen-Xia Han; Bao-Qing Dun; Ji Zhang; Zhi Wang; Yi Sui; Li Zhu; Gui-Ying Li (Planta, 2022)

Effects of nitric oxide on the growth of marine microalgae and carbonate chemistry parameters - Pei-Feng Li; Min Zhao; Chun-Ying Liu; Gui-Peng Yang (Marine Biology, 2022)

Correction to: HOXA11‑AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR‑124 expression by binding to EZH2 - Wen‑long Zhang; Ya‑nan Zhao; Zhang‑zhen Shi; Gui‑ying Gu; Dan Cong; Chen Wei; Yuan‑song Bai (Human Cell, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Synthesis and biological evaluation of novel 1,3-diphenylurea quinoxaline derivatives as potent anticancer agents - Gui-Zhen Li; Xi-Lin Ouyang; Zu-Yu Mo; Yao Gu; Xiao-Lin Cao; Li Yang; Hai-Tao Tang; Ying-Ming Pan (Medicinal Chemistry Research, 2021)

Risk factors for sleep disorders in patients undergoing peritoneal dialysis - Gui-Ling Liu; Qiu-Nan Zhan; You-Lu Zhao; Zu-Ying Xiong; Jin-Lan Liao; Ye-Ping Ren; Qin Wang; Li-Ping Duan; Zhao-Xia Zheng; Li Hao; Jie Dong (Sleep and Biological Rhythms, 2021)
Sleep disorders in patients with end-stage renal disease are common but have rarely been reported in previous studies. Therefore, we examined the prevalence of sleep disorders and the risk factors for declining sleep quality in patients undergoing peritoneal dialysis (PD). A multicenter prospective cohort study was conducted at five PD centers across different provinces in China. A total of 449 patients who underwent PD between March to November 2013 were enrolled. Demographic data, laboratory indicators, presence of depression, and sleep assessment data were collected. Sleep questionnaires reflecting five categories of sleep disorders, namely, insomnia, restless legs syndrome, excessive daytime sleepiness, possible narcolepsy, and sleepwalking and nightmares, were administered at baseline and at 24 months postoperatively. Sleep disorders were diagnosed when a patient had at least one sleep problem. At baseline, 335 (74.6%) patients had at least one type of sleep disorder. Depression, diabetes mellitus (DM), and male were found to be associated with the presence of a sleep disorder. At follow-up, the prevalence of insomnia, restless legs syndrome, and excessive daytime sleepiness had significantly increased in 285 patients. Furthermore, cardiovascular disease (CVD) was found to be associated with the presence of sleep disorders in patients with one or more disorders at baseline, whereas a low serum albumin level was found to be associated with sleep disorders in patients without any sleep disorders at baseline. The prevalence of sleep disorders was relatively high among PD patients at baseline and increased afterthe2-year follow-up. Depression, DM, and male were associated with all sleep disorders at baseline. CVD was associated with the presence of a sleep disorder at baseline and worse sleep quality at the 2-year follow-up; whereas a low serum albumin level was associated with the risk of acquiring a sleep disorder at the 2-year follow-up among patients with normal sleep status at baseline.

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

Occurrence and cycle of dimethyl sulfide in the western Pacific Ocean - Feng Xu; Shi‐Bo Yan; Hong‐Hai Zhang; Ying‐Cui Wu; Qian‐Yao Ma; Yu‐Chen Song; Guang‐Chao Zhuang; Gui‐Peng Yang (Limnology and Oceanography, 2021)
Oceanic production and occurrence of dimethyl sulfide (DMS) and its subsequent ventilation to the atmosphere significantly contribute to the global sulfur cycle and impact the climate regulation. Spatial distributions of DMS, dimethylsulfoniopropionate (DMSP, precursor of DMS), and dimethyl sulfoxide (DMSO, oxidation product of DMS), production and removal processes of DMS (including biological production, microbial consumption, photo‐degradation, and sea‐to‐air exchange), and biogenic contributions to the atmospheric sulfate burden were simultaneously studied in the western Pacific Ocean during winter. Sea surface DMS, DMSP, and DMSO were strongly correlated and had similar distribution patterns. The DMS photo‐degradation efficiency ratio (normalized using incident photon flux density) for ultraviolet B radiation (UVB): ultraviolet A radiation (UVA): photosynthetically active radiation (PAR) was 391: 36: 1. However, considering the solar spectral composition, the actual contributions of UVB, UVA, and PAR to DMS photo‐degradation in surface waters were 40.6% ± 10.7%, 41.2% ± 15.6%, and 18.2% ± 7.2%, respectively. When integrated across the entire mixed layer, UVA and PAR became the dominant drivers, accounting for 45.2% ± 18.0% and 38.0% ± 17.3% of DMS photo‐degradation, respectively, as UVB was significantly attenuated in seawater. The DMS budget of the entire mixed layer indicated that microbial consumption, photo‐degradation, and ventilation accounted for about 74.3% ± 11.9%, 19.3% ± 9.3%, and 6.5% ± 4.0% of total DMS removal, respectively. Even if ventilation was a minor DMS removal pathway, DMS emissions still contributed approximately 45.2% ± 25.6% of the atmospheric non‐sea‐salt sulfate burden over the western Pacific Ocean.

Neuroprotective carbazole alkaloids from the stems and leaves of Clausena lenis - Gui Yan; Yu-Jie Li; Ying-Ying Zhao; Jia-Ming Guo; Wen-Hao Zhang; Ming-Ming Zhang; Yan-Hui Fu; Yan-Ping Liu (Natural Product Research, 2021)

Genetic diversity analysis of Topmouth Culter (Culter alburnus) based on microsatellites and D-loop sequences - Ning Sun; Dong-Mei Zhu; Qing Li; Gui-Ying Wang; Jian Chen; Feifei Zheng; Pei Li; Yan-Hong Sun (Environmental Biology of Fishes, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

The observed synoptic scale precipitation relationship between Western Equatorial Africa and Eastern Equatorial Africa - Godwin Ayesiga; Christopher E. Holloway; Charles JR. Williams; Gui‐Ying Yang; Samantha Ferrett (International Journal of Climatology, 2021)
An improvement to subseasonal (i.e., days to weeks) rainfall prediction across Equatorial Africa is an important area of current research. This is because most countries in this region are highly dependent on rain‐fed agriculture, and so millions of livelihoods are at risk in the event of an unexpected poor harvest. This study examines 16 years of daily precipitation anomalies to investigate the relationship in precipitation between Western Equatorial Africa (WEA) and Eastern Equatorial Africa (EEA). Using lead/lag correlation and spatio‐temporal correlation patterns over various sub‐regions, a synoptic‐scale relationship in precipitation is presented between WEA and EEA, in which precipitation over EEA lags precipitation over WEA by 1–2 days. In addition, central WEA and sub‐regions in South Sudan display a synoptic‐timescale precipitation contrast, suggesting a weak precipitation dipole. Consistent with the known heterogeneity characteristic of Equatorial Africa's precipitation, our findings suggest that the 1–2 days precipitation relationship is dependent upon the sub‐region under investigation. Furthermore, our results indicate a coherent synoptic‐timescale eastward/northeastward propagating signal with a speed of approximately 12 m/s. Composite and correlation analyses of precipitation anomalies and a novel equatorial wave dataset show an apparent connection between eastward/northeastward propagating wet anomalies and Kelvin wave lower‐tropospheric convergence. This suggests that Convectively Coupled Kelvin Waves (CCKWs) play a role in modulating the 1–2 days convection and precipitation propagation between WEA and EEA. These results imply that monitoring the propagation characteristics of CCKWs may be important in synoptic‐timescale forecasting over Equatorial Africa.

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

Changes in functional traits and stoichiometry of Aegiceras corniculatum propagule in three shrimp aquaculture effluent regions - Ying-Ying Qin; Mei-Rong Luo; Min-Zhong Liang; Zhi-Jun Shen; Gui-Feng Gao; Gang Hu; Martin Simon; Shi-Chu Liang; Hai-Lei Zheng (Aquatic Ecology, 2020)

A new indole alkaloid with anti-inflammatory from the branches of Nauclea officinalis - Le-Ling Song; Yan-Ling Mu; Hao-Chao Zhang; Gui-Ying Wu; Jing-Yong Sun (Natural Product Research, 2020)

Bioactive Eudesmane sesquiterpenes from Artabotrys hongkongensis Hance - Qing Wen; Yan-Ping Liu; Gui Yan; Shuo Yang; Shi Hu; Jing Hua; Wen-Qing Yin; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2020)

Influence of Aphis gossypii feeding on defense strategy of native and introduced populations of Ageratina adenophora - Ying Lin; Shu-Qi He; Zhi-Hui Lu; Yu-Lin Gao; Yan-Ru Duan; Zheng-Yue Li; Bin Chen; Fu-Rong Gui (Arthropod-Plant Interactions, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

First report of actinidia virus A and B infecting kiwifruit in Jiangxi province in China - Man Fei Zou; Ming Feng Yan; Ying Zhou; Yuan Xiu Wang; Gui Hong Xiong; Jun Xi Jiang (Journal of Plant Pathology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Combined effects of elevated temperature and pCO2 on the production of DMSP and DMS in the culture of Amphidinium carterae - Pei-Feng Li; Gui-Peng Yang; Chun-Ying Liu (Journal of Applied Phycology, 2020)

Transdermal Administration of Ibuprofen-Loaded Gel: Preparation, Pharmacokinetic Profile, and Tissue Distribution - Meng-qiu Xia; Chun-ling Tian; Liu Liu; Rong-feng Hu; Shuang-ying Gui; Xiao-qin Chu (AAPS PharmSciTech, 2020)

The NADPH oxidase in Volvariella volvacea and its differential expression in response to mycelial ageing and mechanical injury - Jun-Jie Yan; Zong-Jun Tong; Yuan-Yuan Liu; Zi-Yan Lin; Ying Long; Xing Han; Wei-Nan Xu; Qian-Hui Huang; Yong-Xin Tao; Bao-Gui Xie (Brazilian Journal of Microbiology, 2020)

Photoproduction of nitric oxide in seawater - Ye Tian; Gui-Peng Yang; Chun-Ying Liu; Pei-Feng Li; Hong-Tao Chen; Hermann W. Bange (Ocean Science, 2020)
Nitric oxide (NO) is a short-lived intermediate of the oceanic nitrogen cycle. However, our knowledge about its production and consumption pathways in oceanic environments is rudimentary. In order to decipher the major factors affecting NO photochemical production, we irradiated several artificial seawater samples as well as 31 natural surface seawater samples in laboratory experiments. The seawater samples were collected during a cruise to the western tropical North Pacific Ocean (WTNP, a N–S section from 36 to 2∘ N along 146 to 143∘ E with 6 and 12 stations, respectively, and a W–E section from 137 to 161∘ E along the Equator with 13 stations) from November 2015 to January 2016. NO photoproduction rates from dissolved nitrite in artificial seawater showed increasing trends with decreasing pH, increasing temperature, and increasing salinity. In contrast, NO photoproduction rates (average: 0.5±0.2×10-12 mol L−1 s−1) in the natural seawater samples from the WTNP did not show any correlations with pH, water temperature, salinity, or dissolved inorganic nitrite concentrations. The flux induced by NO photoproduction in the WTNP (average: 13×10-12 mol m−2 s−1) was significantly larger than the NO air–sea flux density (average: 1.8×10-12 mol m−2 s−1), indicating a further NO loss process in the surface layer.

Carbazole alkaloids from Clausena emarginata with their potential antiproliferative activities - Yan-Hui Fu; Yan-Lei Ma; Gui Yan; Qing Wen; Shi Hu; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu (Natural Product Research, 2019)

12 β -Acetyloxyperforatin, a New Limonoid from Harrisonia Perforata - Peng-Yan Gui; Xiao-Hui Yan; Wen-Juan Yuan; Yuan-Liang Ma; Xiao Ding; Shuai Liu; Ying-Tong Di; Wei-Ming Zhu; Xiao-Jiang Hao (Natural Product Research, 2019)

HOXA11-AS promotes the migration and invasion of hepatocellular carcinoma cells by inhibiting miR-124 expression by binding to EZH2 - Wen-long Zhang; Ya-nan Zhao; Zhang-zhen Shi; Gui-ying Gu; Dan Cong; Chen Wei; Yuan-song Bai (Human Cell, 2019)

Neurotrophin Receptor p75 mRNA Level in Peripheral Blood Cells of Patients with Alzheimer’s Disease - Yali Xu; Wei-Wei Li; Jun Wang; Chi Zhu; Ying-Ying Shen; An-Yu Shi; Gui-Hua Zeng; Zhi-Qiang Xu; Xin-Fu Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Neisseria chenwenguii sp. nov. isolated from the rectal contents of a plateau pika (Ochotona curzoniae) - Gui Zhang; Jing Yang; Xin-He Lai; Shan Lu; Dong Jin; Ji Pu; Xiangning Bai; Xuelian Luo; Yanwen Xiong; Ying Huang; Cuixia Chen; Jianguo Xu (Antonie van Leeuwenhoek, 2019)

Sema4D expression and secretion are increased by HIF-1α and inhibit osteogenesis in bone metastases of lung cancer - Wu-gui Chen; Jing Sun; Wei-wei Shen; Si-zhen Yang; Ying Zhang; Xu Hu; Hao Qiu; Shang-cheng Xu; Tong-wei Chu (Clinical & Experimental Metastasis, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Polyphenolic compounds from Malus hupehensis and their free radical scavenging effects - Qingwen Hu; Ying-Ying Chen; Qi-Yang Jiao; Afsar Khan; Jimiao Shan; Gui-Dong Cao; Feng Li; Chao Zhang; Hong-Xiang Lou (Natural Product Research, 2018)

Ethanol extract of Rehmannia glutinosa exerts antidepressant-like effects on a rat chronic unpredictable mild stress model by involving monoamines and BDNF - Jun-Ming Wang; Li-Xin Pei; Yue-Yue Zhang; Yong-Xian Cheng; Chun-Ling Niu; Ying Cui; Wei-Sheng Feng; Gui-Fang Wang (Metabolic Brain Disease, 2018)

Chlorogenic acid alleviates autophagy and insulin resistance by suppressing JNK pathway in a rat model of nonalcoholic fatty liver disease - Hua Yan; Yan-Qiong Gao; Ying Zhang; Huan Wang; Gui-Sheng Liu; Jian-Yuan Lei (Journal of Biosciences, 2018)

Integrated in silico–in vitro screening of ovarian cancer peroxisome proliferator-activated receptor-γ agonists against a biogenic compound library - Gui-Lian Zhang; Feng-Ying Liu; Jing Zhang; Li-Ping Wang; Er-Xia Jia; Shi-Ming Lv (Medicinal Chemistry Research, 2018)

Changes in Histopathology, Enzyme Activities, and the Expression of Relevant Genes in Zebrafish (Danio rerio) Following Long-Term Exposure to Environmental Levels of Thallium - Li-Ping Hou; Yang Yang; Hu Shu; Guang-Guo Ying; Jian-Liang Zhao; Yi-Bing Chen; Yong-Heng Chen; Gui-Zhen Fang; Xin Li; Ji-Sheng Liu (Bulletin of Environmental Contamination and Toxicology, 2017)

Potential gray matter unpruned in adolescents and young adults dependent on dextromethorphan-containing cough syrups: evidence from cortical and subcortical study - Ying-wei Qiu; Xiao-fei Lv; Gui-hua Jiang; Huan-Huan Su; Xiao-fen Ma; Jun-zhang Tian; Fu-zhen Zhuo (Brain Imaging and Behavior, 2017)

Determination of dissolved nitric oxide in coastal waters of the Yellow Sea off Qingdao - Chun-Ying Liu; Wei-Hua Feng; Ye Tian; Gui-Peng Yang; Pei-Feng Li; Hermann W. Bange (Ocean Science, 2017)
We developed a new method for the determination of dissolved nitric oxide (NO) in discrete seawater samples based on the combination of a purge-and-trap setup and a fluorometric detection of NO. 2,3-diaminonaphthalene (DAN) reacts with NO in seawater to form the highly fluorescent 2,3-naphthotriazole (NAT). The fluorescence intensity was linear for NO concentrations in the range from 0.14 to 19 nmol L−1. We determined a detection limit of 0.068 nmol L−1, an average recovery coefficient of 83.8 % (80.2–90.0 %), and a relative standard deviation of ±7.2 %. With our method we determined for the first time the temporal and spatial distributions of NO surface concentrations in coastal waters of the Yellow Sea off Qingdao and in Jiaozhou Bay during a cruise in November 2009. The concentrations of NO varied from below the detection limit to 0.50 nmol L−1 with an average of 0.26 ± 0.14 nmol L−1. NO surface concentrations were generally enhanced significantly during daytime, implying that NO formation processes such as NO2− photolysis are much higher during daytime than chemical NO consumption, which, in turn, lead to a significant decrease in NO concentrations during nighttime. In general, NO surface concentrations and measured NO production rates were higher compared to previously reported measurements. This might be caused by the high NO2− surface concentrations encountered during the cruise. Moreover, additional measurements of NO production rates implied that the occurrence of particles and a temperature increase can enhance NO production rates. With the method introduced here, we have a reliable and comparably easy to use method at hand to measure oceanic NO surface concentrations, which can be used to decipher both its temporal and spatial distributions as well as its biogeochemical pathways in the oceans.

Genome-wide identification, characterization, and expression analysis of SnRK2 family in Hevea brasiliensis - Dong Guo; Hui-Liang Li; Jia-Hong Zhu; Ying Wang; Feng An; Gui-Shui Xie; Shi-Qing Peng (Tree Genetics & Genomes, 2017)

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea - Xiao-Dong Shang; Chang-Rong Liang; Gui-Ying Chen (Ocean Science, 2017)
The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of the Luzon Strait, with an average dissipation rate and diapycnal diffusivity of 8.3 × 10−9 W kg−1 and 2.7 × 10−5 m2 s−1, respectively, almost 1 order of magnitude higher than those in the central and southern SCS. In the region to the west of the Luzon Strait, the water column was characterized by strong shear and weak stratification. Elevated dissipation rates (ε > 10−7 W kg−1) and diapycnal diffusivities (κ > 10−4 m2 s−1), induced by shear instability, occurred in the water column. In the central and southern SCS, the water column was characterized by strong stratification and weak shear and the turbulent mixing was weak. Internal waves and internal tides generated near the Luzon Strait are expected to make a dominant contribution to the strong turbulent mixing and shear in the region to the west of the Luzon Strait. The observed dissipation rates were found to scale positively with the shear and stratification, which were consistent with the MacKinnon–Gregg model used for the continental shelf but different from the Gregg–Henyey scaling used for the open ocean.

Observations of the turbulent kinetic energy dissipation rate in the upper central South China Sea - Chang-Rong Liang; Gui-Ying Chen; Xiao-Dong Shang (Ocean Dynamics, 2017)

Rheological behavior of dredged slurries at high water contents - Gui-Zhong Xu; Yu-Feng Gao; Ying Zhang; Ruo-Bing Sun (Marine Georesources & Geotechnology, 2017)

Factors Responsible for Sugarcane Ratoon Chlorosis in Acid Soil and Its Management in Guangxi Province of China - Gui-Fen Chen; Zhong Liu; Yu-Yi Huang; Liu-Mei Xiong; Yu-Mo Tan; Ying Xing; Qi-Zhan Tang (Sugar Tech, 2016)

Transcriptome analysis of sika deer in China - Bo-Yin Jia; Heng-Xing Ba; Gui-Wu Wang; Ying Yang; Xue-Zhe Cui; Ying-Hua Peng; Jun-Jun Zheng; Xiu-Mei Xing; Fu-He Yang (Molecular Genetics and Genomics, 2016)

Sirtuin-3 (SIRT3) protects pancreatic β-cells from endoplasmic reticulum (ER) stress-induced apoptosis and dysfunction - Hao-Hao Zhang; Xiao-Jun Ma; Li-Na Wu; Yan-Yan Zhao; Peng-Yu Zhang; Ying-Hui Zhang; Ming-Wei Shao; Fei Liu; Fei Li; Gui-Jun Qin (Molecular and Cellular Biochemistry, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

The anxiolytic- and antidepressant-like effects of ATPM-ET, a novel κ agonist and μ partial agonist, in mice - Qian Wang; Yu Long; Ai Hang; Gui-Ying Zan; Xiao-Hong Shu; Yu-Jun Wang; Jing-Gen Liu (Psychopharmacology, 2016)

Comparison of vitrified outcomes between human early blastocysts and expanded blastocysts - Wen-yan Song; Xue-gai Wang; Hai-xia Jin; Gui-dong Yao; Xiang-yang Zhang; Sen-lin Shi; Hong-yi Yang; Zhao-feng Peng; Ying-pu Sun (In Vitro Cellular & Developmental Biology - Animal, 2016)

Cotton S-adenosylmethionine decarboxylase-mediated spermine biosynthesis is required for salicylic acid- and leucine-correlated signaling in the defense response to Verticillium dahliae - Hui-Juan Mo; Yan-Xiang Sun; Xiao-Li Zhu; Xing-Fen Wang; Yan Zhang; Jun Yang; Gui-Jun Yan; Zhi-Ying Ma (Planta, 2016)

Follicle-stimulating hormone increases the intramuscular fat content and expression of lipid biosynthesis genes in chicken breast muscle - Xiao-yan Cui; Ying-ying Li; Ran-ran Liu; Gui-ping Zhao; Mai-qing Zheng; Qing-he Li; Jie Wen (Journal of Zhejiang University-SCIENCE B, 2016)

Seroprevalence and risk factors of Mycobacterium avium subspecies paratuberculosis infection in domestic sika deer in China - Qing-Feng Meng; Ying Li; Fan Yang; Gui-Zhi Yao; Ai-Dong Qian; Wei-Li Wang; Wei Cong (Tropical Animal Health and Production, 2015)

Excitotoxicity Induced by Realgar in the Rat Hippocampus: the Involvement of Learning Memory Injury, Dysfunction of Glutamate Metabolism and NMDA Receptors - Tao-guang Huo; Wei-kai Li; Ying-hua Zhang; Jie Yuan; Lan-yue Gao; Yuan Yuan; Hui-lei Yang; Hong Jiang; Gui-fan Sun (Molecular Neurobiology, 2015)

SIRT1 overexpression in skeletal muscle in vivo induces increased insulin sensitivity and enhanced complex I but not complex II–V functions in individual subsarcolemmal and intermyofibrillar mitochondria - Hao-Hao Zhang; Gui-Jun Qin; Xia-Lian Li; Ying-Hui Zhang; Pei-Jie Du; Peng-Yu Zhang; Yan-Yan Zhao; Jing Wu (Journal of Physiology and Biochemistry, 2015)

Molecular Cloning and Characterization of a Short-Chain Dehydrogenase Showing Activity with Volatile Compounds Isolated from Camellia sinensis - Ying Zhou; Ling Zhang; Jiadong Gui; Fang Dong; Sihua Cheng; Xin Mei; Linyun Zhang; Yongqing Li; Xinguo Su; Susanne Baldermann; Naoharu Watanabe; Ziyin Yang (Plant Molecular Biology Reporter, 2015)

Association mapping of salinity and alkalinity tolerance in improved japonica rice (Oryza sativa L. subsp. japonica Kato) germplasm - Di Cui; Chang-ying Xu; Chun-gang Yang; Qi-xing Zhang; Jun-guo Zhang; Xiao-ding Ma; Yong-li Qiao; Gui-lan Cao; San-yuan Zhang; Long-zhi Han (Genetic Resources and Crop Evolution, 2015)

Spatial Distribution of Perfluoroalkyl Substances in Surface Sediments of Five Major Rivers in China - Chang-Gui Pan; Guang-Guo Ying; Jian-Liang Zhao; You-Sheng Liu; Shuang-Shuang Liu; Jun Du; Rai S. Kookana (Archives of Environmental Contamination and Toxicology, 2015)

Differences in responses of soil microbial properties and trifoliate orange seedling to biochar derived from three feedstocks - Ying Zhang; Qiling Tan; Chengxiao Hu; Cangsong Zheng; Huiping Gui; Weinan Zeng; Xuecheng Sun; Xiaohu Zhao (Journal of Soils and Sediments, 2015)

Study on the Diversity of Bacteroides and Clostridium in Patients with Primary Gout - Shi-Chao Xing; Dong-Mei Meng; Ying Chen; Gang Jiang; Xi-Shuang Liu; Na Li; Yao-Yao Yan; Chang-Gui Li (Cell Biochemistry and Biophysics, 2015)

Identification of QTLs associated with salt or alkaline tolerance at the seedling stage in rice under salt or alkaline stress - Jing-long Liang; Ying-ping Qu; Chun-gang Yang; Xiao-ding Ma; Gui-lan Cao; Zheng-wu Zhao; San-yuan Zhang; Tao Zhang; Long-zhi Han (Euphytica, 2015)

Changes of Serum Osteocalcin, Calcium, and Potassium in a Rat Model of Type 2 Diabetes - Lin Xiao; Xian Mo Wang; Tao Yang; Ying Xiong; Zhong Gui Zhang; Jun Ding; Chen Xu; Chang Yuan Xiong (Cell Biochemistry and Biophysics, 2015)

Molecular characterization of a novel reovirus isolated from Pekin ducklings in China - Ying-Qi Zhu; Chuan-Feng Li; Zhuang-Li Bi; Zong-Yan Chen; Chun-Chun Meng; Gui-Jun Wang; Chan Ding; Guang-Qing Liu (Archives of Virology, 2015)

No association between identified multiple sclerosis non-MHC risk loci and neuromyelitis optica - Qi-Bing Liu; Zhen-Xin Li; Gui-Xian Zhao; Hai Yu; Zhi-Ying Wu (Neuroscience Bulletin, 2014)

Coordinated regulation of autophagy and apoptosis determines endothelial cell fate during Dengue virus type 2 infection - Junqi Huang; Ying Li; Yiming Qi; Yingke Zhang; Lin Zhang; Zilian Wang; Xuzhi Zhang; Lian Gui (Molecular and Cellular Biochemistry, 2014)

Elatoside C protects against hypoxia/reoxygenation-induced apoptosis in H9c2 cardiomyocytes through the reduction of endoplasmic reticulum stress partially depending on STAT3 activation - Min Wang; Xiang-bao Meng; Ying-li Yu; Gui-bo Sun; Xu-dong Xu; Xiao-po Zhang; Xi Dong; Jing-xue Ye; Hui-bo Xu; Yi-fan Sun; Xiao-bo Sun (Apoptosis, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Complete genome sequence analysis identifies a new genotype of brassica yellows virus that infects cabbage and radish in China - Xiao-Yan Zhang; Hai-Ying Xiang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2014)

Coumarin-containing aminophosphonates bridged with chiral side chain: synthesis and influence of chirality on cytotoxicity and DNA binding - Ya-Jun Li; Man-Yi Ye; Ri-Zhen Huang; Gui-Yang Yao; Ying-Ming Pan; Zhi-Xin Liao; Heng-Shan Wang (Medicinal Chemistry Research, 2014)

Identification of BACH2 as a susceptibility gene for Graves’ disease in the Chinese Han population based on a three-stage genome-wide association study - Wei Liu; Hai-Ning Wang; Zhao-Hui Gu; Shao-Ying Yang; Xiao-Ping Ye; Chun-Ming Pan; Shuang-Xia Zhao; Li-Qiong Xue; Hui-Jun Xie; Sha-Sha Yu; Cui-Cui Guo; Wen-Hua Du; et al. (Human Genetics, 2014)

Utilization of crop heterosis: a review - Donghui Fu; Meili Xiao; Alice Hayward; Ying Fu; Gui Liu; Guanjie Jiang; Haihuan Zhang (Euphytica, 2014)

Erratum to: Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Cetin Sengonca; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Comparison of lisianthus (Eustoma grandiflorum) cultivars based on the selected regeneration media using anther culture - Xuhong Zhou; Xijun Mo; Suping Qu; Min Tian; Xuewei Wu; Min Wu; Jinze Li; Ying Luo; Jihua Wang; Min Gui (Horticulture, Environment, and Biotechnology, 2014)

Interactive effects of different inorganic As and Se species on their uptake and translocation by rice (Oryza sativa L.) seedlings - Ying Hu; Gui-Lan Duan; Yi-Zong Huang; Yun-Xia Liu; Guo-Xin Sun (Environmental Science and Pollution Research, 2014)

Bacillus bingmayongensis sp. nov., isolated from the pit soil of Emperor Qin’s Terra-cotta warriors in China - Bo Liu; Guo-Hong Liu; Gui-Ping Hu; Sengonca Cetin; Nai-Quan Lin; Jian-Yang Tang; Wei-Qi Tang; Ying-Zhi Lin (Antonie van Leeuwenhoek, 2014)

Role of Angptl4 in vascular permeability and inflammation - Liang Guo; Shao-Ying Li; Fu-Yun Ji; Yun-Feng Zhao; Yu Zhong; Xue-Jun Lv; Xue-Ling Wu; Gui-Sheng Qian (Inflammation Research, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Functional transient receptor potential canonical type 1 channels in human atrial myocytes - Yan-Hui Zhang; Hui-Jun Wu; Hui Che; Hai-Ying Sun; Lik-Cheung Cheng; Xin Li; Wing-Kuk Au; Hung-Fat Tse; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2013)

Variants in the promoter region of CYP7A1 are associated with neuromyelitis optica but not with multiple sclerosis in the Han Chinese population - Gui-Xian Zhao; Ying Liu; Zhen-Xin Li; Chuan-Zhen Lv; Anthony Traboulsee; A. Dessa Sadovnick; Zhi-Ying Wu (Neuroscience Bulletin, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Biodiesel Potential of Nonfood Plant Resources from Tsinling and Zhongtiao Mountains of China - Shuai Xue; Yosef Steinberger; Ji Shi Wang; Gui Ying Li; Xing You Xu; Guang Hui Xie (BioEnergy Research, 2013)

Edaravone Ameliorates Oxidative Damage Associated with Aβ25-35 Treatment in PC12 Cells - Gui-lian Zhang; Wang-gang Zhang; Yun Du; Li Yao; Hong Sun; Ru Zhang; Enqi Liu; Ning Bu; Hai-qin Wu; Lei Zhang; Ting-ting Li; Ying-ying Guo (Journal of Molecular Neuroscience, 2013)

Co-transfection Gene Delivery of Dendritic Cells Induced Effective Lymph Node Targeting and Anti-tumor Vaccination - Yu-Zhe Chen; Gui-Xin Ruan; Xing-Lei Yao; Li-Ming Li; Ying Hu; Yasuhiko Tabata; Jian-Qing Gao (Pharmaceutical Research, 2013)

Effect of dietary vitamin E and selenium supplementation on growth, body composition, and antioxidant defense mechanism in juvenile largemouth bass (Micropterus salmoide) fed oxidized fish oil - Yong-Jun Chen; Yong-Jian Liu; Li-Xia Tian; Jin Niu; Gui-Ying Liang; Hui-Jun Yang; Yuan Yuan; Yun-Qiang Zhang (Fish Physiology and Biochemistry, 2013)

QTL mapping for seedling traits under different nitrogen forms in wheat - Jin-jie Sun; Ying Guo; Gui-zhi Zhang; Ming-gang Gao; Guo-hua Zhang; Fan-mei Kong; Yan Zhao; Si-shen Li (Euphytica, 2013)

Effects of Selenium Intervention on Chronic Fluorosis-Induced Renal Cell Apoptosis in Rats - Shu-ying Yang; Lei Zhang; Ke-ke Miao; Wei Qian; Zi-gui Zhang (Biological Trace Element Research, 2013)

Effect of different dietary protein and lipid levels on growth performance, body composition of juvenile red swamp crayfish (Procambarus clarkii) - Wei-Na Xu; Wen-Bin Liu; Mei-fang Shen; Gui-Feng Li; Ying Wang; Wei-wei Zhang (Aquaculture International, 2013)

Serum lipids and other risk factors for diabetic retinopathy in Chinese type 2 diabetic patients - Hui-yan Zhang; Jian-yong Wang; Gui-shuang Ying; Li-ping Shen; Zhe Zhang (Journal of Zhejiang University-SCIENCE B, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Low-intensity pulsed ultrasound therapy: a potential strategy to stimulate tendon-bone junction healing - Zhi-min Ying; Tiao Lin; Shi-gui Yan (Journal of Zhejiang University-SCIENCE B, 2012)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

DEL RBC transfusion should be avoided in particular blood recipient in East Asia due to allosensitization and ineffectiveness - Chao-peng Shao; Bao-yan Wang; Shi-hui Ye; Wen-li Zhang; Hua Xu; Nai-bao Zhuang; Xiao-ying Wu; Heng-gui Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Simulation of biatrial conduction via different pathways during sinus rhythm with a detailed human atrial model - Dong-dong Deng; Ying-lan Gong; Guo-fa Shou; Pei-feng Jiao; Heng-gui Zhang; Xue-song Ye; Ling Xia (Journal of Zhejiang University-SCIENCE B, 2012)

Isolation and characterization of two YUCCA flavin monooxygenase genes from cultivated strawberry (Fragaria × ananassa Duch.) - Hong Liu; Yang-Yang Ying; Ling Zhang; Qing-Hua Gao; Jing Li; Zhen Zhang; Jing-Gui Fang; Ke Duan (Plant Cell Reports, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

The UDP glucose: flavonoid-3-O-glucosyltransferase (UFGT) gene regulates anthocyanin biosynthesis in litchi (Litchi chinesis Sonn.) during fruit coloration - Zhi Chang Zhao; Gui Bing Hu; Fu Chu Hu; Hui Cong Wang; Zhuan Ying Yang; Biao Lai (Molecular Biology Reports, 2012)

Evaluation of the Use of SCAR Markers for Screening Genetic Diversity of Lentinula edodes Strains - Jing-Yu Liu; Zheng-He Ying; Fang Liu; Xin-Rui Liu; Bao-Gui Xie (Current Microbiology, 2012)

Effects of different dietary wheat starch levels on growth, feed efficiency and digestibility in grass carp (Ctenopharyngodon idella) - Li Xia Tian; Yong Jian Liu; Hui Jun Yang; Gui Ying Liang; Jin Niu (Aquaculture International, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Resolution of 2-nitroalcohols by Burkholderia cepacia lipase-catalyzed enantioselective acylation - Na Li; Shi-Bin Hu; Gui-Ying Feng (Biotechnology Letters, 2012)

Molecular characterization of two genotypes of a new polerovirus infecting brassicas in China - Hai-Ying Xiang; Shu-Wei Dong; Qiao-Xia Shang; Cui-Ji Zhou; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2011)

Comparative studies on tolerance of Medicago truncatula and Medicago falcata to freezing - Li-Li Zhang; Min-Gui Zhao; Qiu-Ying Tian; Wen-Hao Zhang (Planta, 2011)

Fine mapping of the R SC14Q locus for resistance to soybean mosaic virus in soybean - Ying Ma; Da-Gang Wang; Hai-Chao Li; Gui-Jie Zheng; Yong-Qing Yang; Hua-Wei Li; Hai-Jian Zhi (Euphytica, 2011)

Molecular epidemiology of norovirus gastroenteritis in children in Jiangmen, China, 2005–2007 - Ying-chun Dai; Gui-fang Hu; Xu-fu Zhang; Can-lei Song; Wen-long Xiang; Xian-bo Wu; Le-yi Wang; Xi Jiang; Jun Nie (Archives of Virology, 2011)

A novel strain of Beet western yellows virus infecting sugar beet with two distinct genotypes differing in the 5′-terminal half of genome - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Virus Genes, 2011)

Nicotine dependence and serum BDNF levels in male patients with schizophrenia - Xiang Yang Zhang; Mei Hong Xiu; Da Chun Chen; Fu De Yang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2010)

Spatio-Temporal Variability of Soil Respiration of Forest Ecosystems in China: Influencing Factors and Evaluation Model - Ze-Mei Zheng; Gui-Rui Yu; Xiao-Min Sun; Sheng-Gong Li; Yue-Si Wang; Ying-Hong Wang; Yu-Ling Fu; Qiu-Feng Wang (Environmental Management, 2010)

Molecular characterization of two Chinese isolates of Beet western yellows virus infecting sugar beet - Hai-Ying Xiang; Shu-Wei Dong; Hui-Zhong Zhang; Wei-Lin Wang; Min-Quan Li; Cheng-Gui Han; Da-Wei Li; Jia-Lin Yu (Virus Genes, 2010)

Chromosomal localization of rDNA genes and genomic organization of 5S rDNA in Oreochromis mossambicus, O. urolepis hornorum and their hybrid - Hua Ping Zhu; Mai Xin Lu; Feng Ying Gao; Zhang Han Huang; Li Ping Yang; Jian Fang Gui (Journal of Genetics, 2010)

Validity and reliability testing of the Chinese (mainland) version of the 39-item Parkinson’s Disease Questionnaire (PDQ-39) - Wei Luo; Xiao-hong Gui; Bo Wang; Wen-ying Zhang; Zhi-yuan Ouyang; Yi Guo; Bao-rong Zhang; Mei-ping Ding (Journal of Zhejiang University-SCIENCE B, 2010)

Over-expression of caveolin-1 aggravate LPS-induced inflammatory response in AT-1 cells via up-regulation of cPLA2/p38 MAPK - Xue-Jun Lv; Yu-Ying Li; Yong-Juan Zhang; Mei Mao; Gui-Sheng Qian (Inflammation Research, 2010)

Mathematical models of canine right and left atria cardiomyocytes - Ling Xia; Ying-lan Gong; Xiu-wei Zhu; Yu Zhang; Qi Sun; Heng-gui Zhang (Journal of Zhejiang University-SCIENCE B, 2010)

Development of real-time and nested RT-PCR to detect astrovirus and one-year survey of astrovirus in Jiangmen City, China - Ying-chun Dai; Qiao-hua Xu; Xian-bo Wu; Gui-fang Hu; Ya-li Tang; Jian-dong Li; Qing Chen; Jun Nie (Archives of Virology, 2010)

Enhanced salt tolerance of transgenic poplar plants expressing a manganese superoxide dismutase from Tamarix androssowii - Yu Cheng Wang; Guan Zheng Qu; Hong Yan Li; Ying Jie Wu; Chao Wang; Gui Feng Liu; Chuan Ping Yang (Molecular Biology Reports, 2010)

Gender differences in the prevalence, risk and clinical correlates of tardive dyskinesia in Chinese schizophrenia - Xiang Yang Zhang; Da Chun Chen; Ling Yan Qi; Fang Wang; Mei Hong Xiu; Song Chen; Gui Ying Wu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Construction and characterization of a cDNA library from head kidney of Japanese sea bass (Lateolabrax japonicus) - Zhan-tao Shao; Xiao Cong; Jin-duo Yuan; Gui-wen Yang; Ying Chen; Jie Pan; Li-guo An (Molecular Biology Reports, 2009)

Mycorrhizal synthesis of Tuber indicum with two indigenous hosts, Castanea mollissima and Pinus armandii - Li-Ying Geng; Xiang-Hua Wang; Fu-Qiang Yu; Xiao-Juan Deng; Xiao-Fei Tian; Xiao-Fei Shi; Xue-Dan Xie; Pei-Gui Liu; Yu-Ying Shen (Mycorrhiza, 2009)

Superoxide dismutase and cytokines in chronic patients with schizophrenia: association with psychopathology and response to antipsychotics - Xiang Yang Zhang; Dong Feng Zhou; Ling Yan Qi; Song Chen; Lian Yuan Cao; Da Chun Chen; Mei Hong Xiu; Fan Wang; Gui Ying Wu; Lin Lu; Therese A. Kosten; Thomas R. Kosten (Psychopharmacology, 2009)

Lower serum cytokine levels in smokers than nonsmokers with chronic schizophrenia on long-term treatment with antipsychotics - Xiang Yang Zhang; Lian Yuan Cao; Cai Song; Gui Ying Wu; Da Chun Chen; Ling Yan Qi; Fan Wang; Mei Hong Xiu; Song Chen; Yingyang Zhang; Lin Lu; Therese A. Kosten; et al. (Psychopharmacology, 2008)

Cloning and characterization of a calcium dependent protein kinase gene associated with cotton fiber development - Quan-Sheng Huang; Hai-Yun Wang; Peng Gao; Guo-Ying Wang; Gui-Xian Xia (Plant Cell Reports, 2008)

Population genetics of Ageratina adenophora using inter-simple sequence repeat (ISSR) molecular markers in China - Fu-Rong Gui; Fang-Hao Wan; Jian-Ying Guo (Plant Biosystems, 2008)

Complete sequence analysis reveals two distinct poleroviruses infecting cucurbits in China - Hai-ying Xiang; Qiao-xia Shang; Cheng-gui Han; Da-wei Li; Jia-lin Yu (Archives of Virology, 2008)

Enhanced expression of phospholipase C 1 (ZmPLC1) improves drought tolerance in transgenic maize - Chun-Rong Wang; Ai-Fang Yang; Gui-Dong Yue; Qiang Gao; Hai-Ying Yin; Ju-Ren Zhang (Planta, 2008)

Characterization of donor genome contents of backcross progenies detected by SSR markers in rice - Zhang-Ying Xi; Feng-Hua He; Rui-Zhen Zeng; Ze-Min Zhang; Xiao-Hua Ding; Wen-Tao Li; Gui-Quan Zhang (Euphytica, 2008)

Effect of SPLUNC1 protein on the Pseudomonas aeruginosa and Epstein-Barr virus - Hou-De Zhou; Xiao-Ling Li; Gui-Yuan Li; Ming Zhou; Hua-Ying Liu; Yi-Xing Yang; Tan Deng; Jian Ma; Shou-Rong Sheng (Molecular and Cellular Biochemistry, 2008)

Involvement of voltage-gated K+ and Na+ channels in gastric epithelial cell migration - William Ka Kei Wu; Gui Rong Li; Tak Ming Wong; Jian Ying Wang; Le Yu; Chi Hin Cho (Molecular and Cellular Biochemistry, 2008)

Alteration of mitochondrial oxidative capacity during porcine preadipocyte differentiation and in response to leptin - Gui-Fen Luo; Tai-Yong Yu; Xu-Hui Wen; Ying Li; Gong-She Yang (Molecular and Cellular Biochemistry, 2007)

Osmotic solute responses of mycorrhizal citrus (Poncirus trifoliata) seedlings to drought stress - Qiang-Sheng Wu; Ren-Xue Xia; Ying-Ning Zou; Gui-Yuan Wang (Acta Physiologiae Plantarum, 2007)

BRD7 suppresses the growth of Nasopharyngeal Carcinoma cells (HNE1) through negatively regulating β-catenin and ERK pathways - Cong Peng; Hua Ying Liu; Ming Zhou; Li Ming Zhang; Xiao Ling Li; Shou Rong Shen; Gui Yuan Li (Molecular and Cellular Biochemistry, 2007)

Effects of biological soil crusts on emergence of desert vascular plants in North China - Yan-Gui Su; Xin-Rong Li; Ying-Wu Cheng; Hui-Juan Tan; Rong-Liang Jia (Plant Ecology, 2007)

Association of functional catechol O-methyl transferase (COMT) Val108Met polymorphism with smoking severity and age of smoking initiation in Chinese male smokers - Song Guo; Da Fang Chen; Dong Feng Zhou; Hong Qiang Sun; Gui Ying Wu; Colin N. Haile; Therese A. Kosten; Thomas R. Kosten; Xiang Yang Zhang (Psychopharmacology, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

The effects of Ginkgo biloba extract added to haloperidol on peripheral T cell subsets in drug-free schizophrenia: a double-blind, placebo-controlled trial - Xiang Yang Zhang; Dong Feng Zhou; Lian Yuan Cao; Gui Ying Wu (Psychopharmacology, 2006)

Rapid Detection of Avian Influenza Virus A and Subtype H5N1 by Single Step Multiplex Reverse Transcription-polymerase Chain Reaction - Hui-Ling Wei; Gui-Rong Bai; Aaron S. Mweene; Ying-Chun Zhou; Yan-Long Cong; Juan Pu; Shuai Wang; Hiroshi Kida; Jin-Hua Liu (Virus Genes, 2006)

The influence of feeding rate on growth, feed efficiency and body composition of juvenile grass carp (Ctenopharyngodon idella) - Zhen-Yu Du; Yong-Jian Liu; Li-Xia Tian; Jian-Guo He; Jun-Ming Cao; Gui-Ying Liang (Aquaculture International, 2006)

Mutation analysis of 218 Chinese patients with Wilson disease revealed no correlation between the canine copper toxicosis gene MURR1 and Wilson disease - Zhi-Ying Wu; Gui-Xian Zhao; Wan-Jin Chen; Ning Wang; Bo Wan; Min-Ting Lin; Shen-Xing Murong; Long Yu (Journal of Molecular Medicine, 2006)

Tissue distribution of the secretory protein, SPLUNC1, in the human fetus - Hou-De Zhou; Song-Qin Fan; Jin Zhao; Dong-Hai Huang; Ming Zhou; Hua-Ying Liu; Zhao-Yang Zeng; Yi-Xing Yang; He Huang; Xiao-Ling Li; Shou-Rong Shen; Gui-Yuan Li (Histochemistry and Cell Biology, 2006)

Prolactin levels in male schizophrenic patients treated with risperidone and haloperidol: a double-blind and randomized study - Xiang Yang Zhang; Dong Feng Zhou; Lian Yuan Cao; Pei Yan Zhang; Gui Ying Wu; Yu Cun Shen (Psychopharmacology, 2005)

Improved cell growth and Taxol production of suspension-cultured Taxus chinensis var. mairei in alternating and direct current magnetic fields - Gui-Min Shang; Jin-Chuan Wu; Ying-Jin Yuan (Biotechnology Letters, 2004)